Optimal Uncertainty: Flexibility and Innovation for The Future of Work - Griffin, Mark (2019)
The nature of work is rapidly evolving as technological, demographic, and economic changes influence all aspects of our society. The changing nature of work requires a more wholistic understanding of work-life systems. In this presentation, I explore uncertainty as a key concept in understanding modern work-life systems. Uncertainty is a defining feature of complex, and high-risk work and often viewed as a contextual feature of the work context. I review recent research investigating uncertainty as a more dynamic element of work-life that is both generated and managed when there is a need for ongoing adaptive behaviour. I review recent research investigating how individuals both respond to and generate uncertainty to be adaptive and introduce the notion of optimal uncertainty. I present our current framework for thinking about the skills and abilities needed to be effective in a digitally connected and uncertain world.